Holocene sediment distribution in the Al Wajh platform lagoon (northern Red Sea, Saudi Arabia), a modern analogue for large rift basin carbonate platforms. Issue 3 (9th December 2021) - Petrovic, Alexander; Ariza Fuentes, Manuel; Putri, Indah; Yahaya, Liyana Nur; Khanna, Pankaj; Purkis, Sam J.; Vahrenkamp, Volker
Abstract: Sedimentary patterns and hydrodynamic transport processes on modern carbonate platforms in arid climates are understudied compared to platforms in humid‐tropical climates. The Al Wajh platform – located in the Arabian–African desert belt – is a large land‐attached carbonate platform in the Red Sea providing an excellent opportunity to fill this gap. The platform covers some 1800 km 2 and is almost completely enclosed by a 115 km long reef‐shoal belt. More than 200 sediment surface samples were analyzed in order to investigate the lateral sediment distribution within the lagoon. The seafloor map was refined integrating sample depths with previous published bathymetric information. Conductivity and temperature profiles were measured to study the lagoonal water body. The lagoon is dominated by poorly sorted, sand‐sized sediments with low total organic carbon content, while carbonate fines content shows significant lateral variation. Aragonite dominates sediment mineralogy with high‐Mg calcite and low‐Mg calcite being significant admixtures. Fine‐grained siliciclastics are found across the entire lagoon, with angular quartz locally enriched in nearshore and distal areas. Seven component assemblages are defined ranging from benthic foraminifera and mollusc‐rich to reef debris‐rich component assemblages. Platform‐interior ooids are for the first time documented from the modern Red Sea. The heterogeneous distribution of carbonate fines shows no water depth related trends, while the component assemblage arrangement is depth related. Hydrodynamics are interpreted to be the main mechanism controlling carbonate fines distribution in the lagoon. A nearshore enrichment of angular sand‐sized quartz suggests influx through wadis during flash floods, while an almost even distribution of fine‐grained siliciclastics possibly indicate aeolian import. These findings provide new insights to the importance of hydrodynamic transport processes for sediment distribution in a land‐attached platform lagoon in an arid climate. Finally, this study presents a comparison with other modern platforms and discusses implications for improving strategies of hydrocarbon field development in rift‐basin carbonates.